Design of Pusher-Arm Structure and Service Reliability Research for Oilfield Small Repair Well Operation Robot - Yang, Fanyeqi; Wang, Yansong (International Core Journal of Engineering, 2025)
To address the issues of low efficiency in manual operation and high safety risks during the tripping operation of small workover tubing in oilfields, this study proposes a functionally integrated pusher arm structure. The lifting slide rail module enables precise Z-axis positioning, the two-stage rotating arm controls the horizontal trajectory, and the crank-slider hydraulic clamp performs adaptive grasping, achieving the fully automatic transportation of Ø73-339.7mm tubing from the catwalk to the wellhead. The study combines the theoretical mechanics model with finite element simulation to systematically verify the structural reliability of key components under a 1500N limit load. UG software is employed to build a three-dimensional model and optimize the sectional moment of inertia. ANSYS Workbench is utilized for static and transient dynamic analysis, and ADAMS-AMESim co-simulation is used to verify the dynamic performance. The results indicate that the 45-steel fixture has a maximum stress of 76.58 MPa (with a safety factor of 3.36), the Q235 rotating arm has a maximum stress of 36.78 MPa (with a safety factor of 4.2), and the positioning accuracy can reach ±5 mm. After integrating the system into a 40-ton workover rig, the manual intervention at the wellhead is reduced by 82%, and the time for tripping a single tubing is shortened from 4.5 minutes to 2.1 minutes, which provides key technical support for the automation of oilfield workover operations.